The political participation in the history (2016)
The present work studies the algid moments for those that have passed political conceptions through history. This article is divided into three parts corresponding with each historical moment, in which prevailed one or other of these conceptions. The first moment is the classical antiquity, the second one is the period extending from imperial Rome until last years of Middle Age and the third moment corresponds to the contemporary era. At this point it is important to take into account that the political conceptions that were studied at each historical moment correspond to the major theories of political power described by Ullmann: ascending and descending. Under the first, the political system is metaphorically conceived as a pyramid, being citizens its base, where the whole power is concentrated. The political conception understood as descending, says that theoriginal power resides in God, who gives the laws to humanity through the kings.